Incorporation of a liquid crystal to enhance the luminescence properties of Langmuir-Blodgett films of OC1OC6-PPV - Ferreira, Marystela; Balogh, Debora T.; Giacometti, Jose A.; Olivati, Clarissa A. [UNESP] (Elsevier B.V., 2009)
The control of molecular architecture provided by the Langmuir-Blodgett (LB) method allows one to obtain enhanced luminescence properties in polymer films, which can be exploited in polymer light emitting diodes (PLEDs). In this study, we show that incorporating a liquid crystal (LC) (PCH302/304) into poly-(2-methoxy-5-hexyloxy-p-phenylene-vinylene) (OC1OC6-PPV) in LB films leads to a 4-fold increase in photoluminescence and 2-fold increase in electroluminescence for (ITO/OC1OC6-PPV(LC5%)/Al) devices for emission at 585 nm, with the current vs. voltage (I vs. V) characteristics exhibiting a typical behavior of rectifying diode. The enhanced luminescence was attributed to an efficient separation of emitting OC1OC6-PPV units induced by the LC in the LB film, which were less ordered than LB films from neat OC1OC6-PPV. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Langmuir-Blodgett films; Photoluminescence; Properties; OC1OC6-PPV